2018
DOI: 10.1016/j.ijheatmasstransfer.2018.03.073
|View full text |Cite
|
Sign up to set email alerts
|

The effect of lateral thermal coupling between parallel microchannels on two-phase flow distribution

Abstract: Evaporating flows in parallel channels occurring in a variety of industrial heat exchange processes can encounter nonuniform flow distribution between channels as a result of two-phase flow instabilities.Such flow maldistribution can have a negative impact on the performance, robustness and predictability of these systems. Two-phase flow modeling can assist in understanding the mechanistic behavior of this flow maldistribution, as well as determine parametric trends and identify safe operating conditions. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Parallel micro-channels, functioning as fluid distributors to segregate a singular inlet stream into multiple branches, are ubiquitously employed across a vast array of industrial apparatus, including reactors [1], mixers [2], and heat exchangers [3], among others. Notably, the fluidic properties undergo significant alterations when the system dimensions are scaled down to the micro-scale, defined by a diameter range of 1 µm to 1000 µm [4].…”
Section: Introductionmentioning
confidence: 99%
“…Parallel micro-channels, functioning as fluid distributors to segregate a singular inlet stream into multiple branches, are ubiquitously employed across a vast array of industrial apparatus, including reactors [1], mixers [2], and heat exchangers [3], among others. Notably, the fluidic properties undergo significant alterations when the system dimensions are scaled down to the micro-scale, defined by a diameter range of 1 µm to 1000 µm [4].…”
Section: Introductionmentioning
confidence: 99%
“…It can also maintain a more uniform wall temperature and requires less pumping power compared to a single-phase coolant for equivalent performance [6]. Despite the benefits of dissipating higher heat flux, two-phase flow boiling in microspaces encounters some critical problems like flow instability, premature dry out, lower heat transfer coefficient, and pressure drop during boiling [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The temperature difference between the channels was relatively small due to redistribution of heat through the conductive substrate. The effect of thermal coupling between parallel channels on the flow distribution was theoretically investigated by Van Oevelen et al [22] by additionally accounting for heat conduction in their previous model [13]. By quantifying the flow maldistribution in parallel-channel systems having varying strengths of inter-channel thermal coupling, it was shown that increasing thermal coupling damped the severity of the flow maldistribution.…”
mentioning
confidence: 99%